Paraneoplastic Hypercoagulability – a clinical case with a rapid fatal evolution - Leite, Emília; Mendes, Ana; Oliveira, Emília; Ferreira, Carlos; Santos, J. Meneses (Portuguese Journal Internal Medicine, 2003)
The authors present a case of paraneoplastic hypercoagulability that occurred as the first manifestation of neoplasia. A variable and rapidly fatal clinical course occurred and the neoplasia was only clearly identified at autopsy. The article includes some general theoretical considerations on the physiopathological mechanisms possibly involved in the origin of this type of paraneoplastic disorder, its possible clinical manifestations and on some therapeutic proposals..